Emerging North American investment regime. - EDEN, Lorraine (1996)
Argues that an international regime in cross-border trade and investment is emerging in North America, organised around three policy areas : international trade, investment and tax policies. Notes that recent changes in these areas in North America show how a strong and deep investment regime is emerging at the regional level, based on the national treatment standard. Outlines some problems which continue to hamper the formation of a North American investment standard. Proposes some possible solutions that would facilitate deeper integration.